2014
DOI: 10.1111/nep.12186
|View full text |Cite
|
Sign up to set email alerts
|

Cinacalcet for hypercalcaemic secondary hyperparathyroidism after renal transplantation: a multicentre, retrospective, 3‐year study

Abstract: In renal transplant patients with hypercalcaemic SHPT, cinacalcet controlled serum calcium, iPTH and phosphorus levels up to 3 years. Tolerability was good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…However, its use in kidney transplant recipients remains off-label. Several prospective [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and retrospective [31][32][33][34][35][36][37][38][39][40][41] observational cohort studies have examined the potential effects of cinacalcet in kidney transplant recipients. Most of these studies have included small cohorts with short follow-up periods, whereas only 4 studies have reported follow-up of greater than 3 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its use in kidney transplant recipients remains off-label. Several prospective [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and retrospective [31][32][33][34][35][36][37][38][39][40][41] observational cohort studies have examined the potential effects of cinacalcet in kidney transplant recipients. Most of these studies have included small cohorts with short follow-up periods, whereas only 4 studies have reported follow-up of greater than 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have included small cohorts with short follow-up periods, whereas only 4 studies have reported follow-up of greater than 3 years. 30,38,39,41 More recently, the first double-blind, randomized controlled trial 42 with 1-year follow-up compared cinacalcet versus placebo in kidney transplant recipients with persistent secondary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Препарат, как указывалось выше, не только хорошо контролирует гиперкальциемию, но и подавляет функцию ОЩЖ, не оказывая влияния на функцию пересаженной почки [20,35]. Однако данные публикаций о влия-нии цинакальцета на костный метаболизм оказались противоречивыми.…”
Section: лечение посттрансплантационного гптunclassified
“…In renal transplant patients, several reports and a recent RCT showed that cinacalcet effectively corrected the hypercalcemia and hypophosphatemia associated with persistent hyperparathyroidism (42,43), although no beneficial effect was observed in the percent change in bone mineral density (43).…”
Section: Cinacalcet Use In Patients With Ckd Who Are Not On Dialysismentioning
confidence: 99%